Evaluation of Airborne Lead Pollution and Its Association with Children's Urinary Lead Levels - Alhesnawi, Asaad Sh. M.; Muhammad Hassoun, Batool; Jabbar Madi, Safaa; Haider Jawad, Lubab (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2023)
Despite the measures taken by most countries, lead pollution still poses an environmental and health risk to humans, especially children. Therefore, the current study aims to evaluate lead in the air and its impact on children's health. Lead samples from the air and children's urine were collected from three different areas within Kerbala Governorate: the urban city center residential areas, and rural areas as a reference area for comparison. A suspended dust collector was used to collect lead samples, and then the lead concentration was measured using an atomic spectrometer after digesting them with acids. The results of the study showed that the highest concentration of lead was in the center of the urban area (3.150 ?g/m3) and its mean concentration in the air was 1.703 (?g/m3), which is higher than the US Environmental Protection Agency limits, with statistically significant differences between the study areas p < 0.01. The mean concentration of lead in children's urine was 0.622 (?g/dL) with statistically significant differences between the areas p < 0.01. Pearson's correlation coefficient indicated a significant positive correlation between the concentration of lead in the air and children's urine (r = 0.651; p < 0.05). This means that high lead concentrations in children's urine are due to lead air pollution and are an indicator of lead pollution in the environment and warn of potential risks to children's health. Therefore, the study recommends reducing lead emission sources and conducting periodic examinations.